Interaction of Dibromomethylimidazolium Ion with Trihalomethanesulfonates (CX3SO3–, Where X = F, Cl, Br and H): A Model for Organic Ionic Liquids - Muteri, Seif; M. Soliman, Saied; I. Ismail, Ali; M. Zaid, Mohamed; El Massry, Abdel-Moneim; Lasri, Jamal (Asian Journal of Chemistry, 2014)
The imidazolium ion is a typical species that is used for providing the cation part in the organic ionic liquid. The DFT calculations on the interaction between dibromomethylimidazolium cation and trihalomethane sulfonates, CX3SO3– where X = F, Cl, Br and H, have been performed. The intermolecular interactions which usually control the properties of these organic liquids were investigated based on DFT calculations. It was found that intramolecular interaction is most favored when X is equal to H. These interactions in the complex units were found to depend on the electrostatic force between the positively charged Br-atoms in the dibromomethylimidazolium and the free O2-atom in the CX3SO3– ion. The overlap between the HOMO of the CX3SO3– as electron-rich Lewis base and the empty LUMO of the dibromomethylimidazolium cation indicates that these interactions are orbitally controlled.